The Functional Polymorphism of DDAH2 rs9267551 Is an Independent Determinant of Arterial Stiffness - Averta, Carolina; Mancuso, Elettra; Spiga, Rosangela; Miceli, Sofia; Succurro, Elena; Fiorentino, Teresa Vanessa; Perticone, Maria; Mannino, Gaia Chiara; Thamtarana, Prapaporn Jungtrakoon; Sciacqua, Angela; Sesti, Giorgio; Andreozzi, Francesco (Frontiers in Cardiovascular Medicine, 2022)
Background The association of circulating asymmetric dimethylarginine (ADMA) levels with cardiovascular risk and arterial stiffness has been reportedly demonstrated, although the causal involvement of ADMA in the pathogenesis of these conditions is still debated. Dimethylaminohydrolase 2 (DDAH2) is the enzyme responsible for ADMA hydrolysis in the vasculature, and the functional variant rs9267551 C, in the 5’-UTR of DDAH2, has been linked to increased DDAH2 expression and lower circulating ADMA levels. Approach and Results The study was approved by the Institutional Ethics Committee of the University “Magna Graecia” of Catanzaro (approval code: 2012.63). We genotyped rs9267551 in 633 adults of European ancestry. After correction for age, sex and BMI, carotid–femoral pulse wave velocity (cfPWV), the gold-standard measure of arterial stiffness, resulted significantly lower in rs9267551 C allele carriers (Δ=-1.12 m/s, P<0.01), and a univariate regression showed that the presence of rs9267551 C variant was negatively associated with cfPWV (β=-0.110, P<0.01). In a multivariable regression model, subjects carrying the rs9267551 C allele manifested significantly lower cfPWV than GG carriers (β=-0.098, P=0.01) independently from several potential confounders. We measured circulating ADMA levels in a subset of 344 subjects. A mediation analysis revealed that the effect of DDAH2 rs9267551 genotype on cfPWV was mediated by the variation in ADMA levels. Conclusions These evidences hint that the presence of rs9267551 C allele may explain, at least in part, a reduction in vessel rigidity as measured by cfPWV, and support the attribution of a causative role to ADMA in the pathogenesis of arterial stiffness.